厦门海滨湿地鸟类的研究(1999～2000) - 方文珍; 陈志鸿; 林清贤; 陈小麟 (2002)
1999年 7月至 2 0 0 0年 5月对厦门海滨湿地 12个样区鸟类的种类和数量进行了调查 .结果显示 ;厦门海滨湿地鸟类共有 2 1科 77种 .其优势种有白鹭 (Egrettagarzetta)、黑腹滨鹬 (Calidrisalpina)、环颈 (Charadriusalexan drinus)、普通鸬鹚 (Phalacrocoraxcarbo)、凤头潜鸭 (Aythyaferina)和红嘴鸥 (Larusridibundus) .常见种有白鹭 (E grettagarzetta)、池鹭 (Ardeolabacchus)、环颈 (Charadriusalexandrinus)和矶鹬 (Tringahypoleucos) .在厦门的滨海湿地鸟类组成中 ,有小杓鹬 (Numeniusminutus)、黄嘴白鹭 (Egrettaeulophotes)、黑嘴鸥 (Larussaundersi)和小青脚鹬(Tringaguttifer) 4种国际濒危鸟类 ,有 14种国家 2级保护鸟类 .本次调查第一次发现白脸鹭在中国的新记录 .本文对厦门滨海湿地鸟类的地理区系、居留情况以及种群数量季节变动也进行分析讨论 A survey on species abundance and population fluctuation of the wetland birds in 12 sample areas along Xiamen coastline were carried out from July 1999 to May 2000. 77 species belonging to 21 families were recorded. The dominant species in population size were Little Egret (Egretta garzetta), Dunlin (Calidris alpina), Kentish Plover (Charadrius alexandrinua), Great Cormorant (Phalacrocorax carbo), Tufted Duck (Aythya fuligula), and Black-headed Gull (Larus ridibundus). The most widespread species, commonly distributing in every sample areas were Little Egret, Chinese Pond Heron (Ardeola bacchus), Kentish Plover and Common Sandpiper (Tringa hypoleucos). In the avian fauna of the Xiamen coastline wetland, 4 species of birds were endangered (IUCN, 1996) which were Little Curlew (Numenius minutus) (EN),Chinese Egret (Egretta eulophotes) (V), Saunders's Gull (Larus saundersi) (R) and Nordmann's greenshank (Tringa guttifer) (I), and 14 species were listed as the national second-grade wildlife for protection in China. The White-faced Heron (Egretta novaehollandiae) was firstly recorded in China and Black-shouldered Kite (Elanus caeruleus) was a new record in Fujian Province. The zoogeographic composition and residence status of the avian fauna, and the seasonal change of population size were further analyzed in the paper. 福建省自然科学基金资助项目 (D9910 0 0 3)